Unravelling the key factors in the chlorine-promoted epoxidation of ethylene over a silver–copper oxide nanocatalyst. Issue 19 (10th May 2022) - Urbiztondo, Miguel; Ramirez, Adrian; Hueso, Jose L.; Santamaria, Jesus; Ruiz-Salvador, A. Rabdel; Hamad, Said
Abstract : This work explores the enhanced selectivity of a silver–copper oxide nanocatalyst towards the epoxidation of ethylene. Experimental and DFT calculations suggest the co-existence of indirect and direct pathways and the influence of desorption rates. Abstract : Ethylene oxide is one of the most important raw materials in the chemical industry, with an annual production close to 35 million metric tons. Despite its importance, to date, no metal has been found that can compete with the original silver bulk material catalyst discovered in 1931. Recently, a few copper and copper–silver based nanostructures have demonstrated remarkable selectivity and activity, especially when coupled with an industrial chlorine promoter. The present work evaluates the mechanistic role of chlorine as an active promoter of the selective oxidation of ethylene to ethylene oxide in the presence of a silver–copper oxide hybrid nanocatalyst (AgCuO). Experimental kinetic studies combined with density functional theory (DFT) calculations provide insight into the influence that Ag/CuO-supported chlorine atoms have over the ethylene epoxidation reaction. Remarkably, the typically described indirect route via the formation of an oxametallacycle (OMC) is also accompanied by a direct route. Furthermore, the presence of chlorine seems to facilitate a more favorable adsorption energy for ethylene oxide (EO) than for acetaldehyde (AA), the main reaction by-product. As a result, complete oxidation of EO can be further prevented in the presence of this AgCuO hybrid heteronanostructure.